Comparative Study of Fungal Diversity in the Agricultural soil and Non-agricultural soil of Bhadravathi taluk, Shimoga district, Karnataka, India - KJ, Naveenkumar; B, Thippeswamy; BV, Thirumalesh; K, Pradeepa; Venkatesh (Journal of Research in Biology, 2011)
Fungi play an important role in the maintenance and survival of tropical forests. In the present study, both agricultural soil and non-agricultural soil samples were studied for screening and detection of fungal diversity in these two samples. Three different methods were subjected for the diversity analysis of fungi. Among all the methods serial dilution method is better compared to the baiting technique and war cup method. One gram of leaf litter soil sample was added into the 10 ml of sterile distilled water and mixed well. Then, PDA media was prepared and poured into sterile petriplates and allowed to solidify. The serial dilutions were prepared and 0.1 ml of each dilution were transferred to sterile plates containing PDA media. In non-agricultural soil, four samples were screened for fungal diversity. A total of 14 fungal genera were recorded in all the four samples. In agricultural soil, four samples were screened for fungal diversity. A total of 12 fungal genera were recorded in all the four samples. Umblebylu sample shows more fugal diversity than Kuvempu University Campus, Lakkavalli and Back water of Bhadra reservoir. In agricultural soil sample, maize field shows more fungal diversity than groundnut field, paddy field and sugarcane field